Yellow Pufferfish of Batang Saribas, Sarawak - Azimah, binti Apendi (Universiti Malaysia Sarawak (UNIMAS), 2014)
Yellow pufferfish or Xenopterus naritus (Tetraodontiformes: Tetraodontidae) is a brackish water or estuarine species. In Malaysia, the species can be found abundantly in the state of Sarawak and a well-known species in Batang Saribas, Sarawak from June to September. The species has economic value to the local people and ecological value on the mangrove and estuarine area of Batang Saribas. There are several studies that had been done on yellow pufferfish, but the molecular aspects of this species in Batang Saribas is still lacking. A total of 4 male yellow pufferfish were collected and examined. All the yellow pufferfish were yellowish in color and torpedo-like shape. The standard length was 14.85±0.191 cm and the total length was 18.33±0.583 cm. The number of soft dorsal fins was 31-33 and the soft anal fins were 26-27. Total DNA extraction using modified Doyle & Doyle (1987) was successful where only one individual showing pure DNA (OD260/OD230 ~1.80). The PCR of cytochrome b, Cytochrome Oxidase I and 16S RNA genes were still at optimization stage.